ANALISIS EFEKTIVITAS DAN EFISIENSI SISA HASIL USAHA (SHU) PADA PRIMKOPPOL RESOR BREBES - Absor, Ulul; Rahayu, Sri; Handayani, Sri Ratih; Halida, Soraya Nur (Jurnal Strategik, 2025)
This study takes the title "Analysis of the Effectiveness and Efficiency of the Remaining Operating Result (SHU) at Primkoppol Resort Brebes". Data collection in the study was carried out by collecting recorded financial report data and submitted to cooperative members every year. The financial report data is from 2016 to 2024. While the analysis used in this study is to calculate the realization, effectiveness and efficiency of the Remaining Operating Result (SHU) and to calculate the projection of the Remaining Operating Result (SHU) using the linear trend formula.The results of the research that has been carried out are the target and realization of the acquisition of the Remaining Operating Result (SHU) of Primkoppol Resort Brebes for the period 2016 to 2024 experienced a development rate of 4.76 percent or an average increase of Rp. 411,265,447.42 each year.While the level of effectiveness of the Remaining Operating Result of Primkoppol Resort Brebes for the period 2016 to 2024 has a very good or very effective level of effectiveness. This is because in that period of the year it had an average level of effectiveness of 461.78 percent.The efficiency level of the Remaining Operating Results (SHU) of the Brebes Resort Primkoppol for the period 2016 to 2024 had an average level of 41.43 percent. This can be interpreted that the efficiency level of the Remaining Operating Results (SHU) of the Brebes Resort Primkoppol is good or efficient because it is below 100 percent. Keywords: Effectiveness, Efficiency, Remaining Business Results